Collapse of Memory - Memory of Collapse Narrating Past, Presence and Future about Periods of Crisis - Schiedermair, Joachim; Sasunkevich, Volha Olga (2019)
The attraction of crises keeps going an entire sector of the media industry. Authors, painters, photographers and directors tell fascinating stories about the decline of empires and democracies as much as earthquakes and infectious diseases. Hereby, catastrophe and collapse evolve as a complex construct of experience, interpretation and emotion. The resulting narrative combines analyses of facts about the collapse with a retrospect evaluation, update and confirmation of these facts in the cultural memory of a given society. The random occurrence becomes a memorable event. The contributors of this volume have taken a narratological approach in examining collapse, disaster, catastrophe and how these in turn manifest themselves across different types of media.